A method to produce fully characterized ubiquitin covalently modified by 4-hydroxy-nonenal, glyoxal, methylglyoxal, and malondialdehyde. (3rd March 2016) - Colzani, Mara; Criscuolo, Angela; Casali, Gaia; Carini, Marina; Aldini, Giancarlo
ABSTRACT: Reactive carbonyl species (RCS) and the corresponding protein adducts (advanced glycoxidation or lipoxidation end products, i.e. AGEs and ALEs) are now widely studied from different points of view, since they can be considered as biomarkers, pathogenic factors, toxic mediators and drug targets. One of the main limits of the research in this field is the lack of standardized and fully characterized AGEs and ALEs to be used for biological, toxicological, and analytical studies. In this work, we set up a procedure to prepare and fully characterize a set of AGEs and ALEs by incubating ubiquitin – a model protein selected as target for carbonylation – with four different RCS: 4-hydroxy- trans -2-nonenal (HNE), methylglyoxal (MGO), glyoxal (GO), and malondialdehyde (MDA). After 24 h of incubation, the extent of protein carbonylation was estimated using a recently developed quantitative strategy based on high-resolution mass spectrometry. The resulting AGEs and ALEs were fully characterized by both intact protein and bottom-up analyses in terms of: stoichiometry of the total amount of modified protein, elucidation of the structure of the RCS-deriving adducts, and localization of the RCS-modified amino acids. Each RCS exhibited different reactivity toward ubiquitin, as detected by quantifying the extent of protein modification. The order of reactivity was MGO > GO > HNE > MDA. A variety of reaction products was identified and mapped on lysine, arginine, and histidine residues of the protein. In summary, a highly standardized and reproducible method to prepare fully characterized AGEs/ALEs is here presented.